Genome-Wide Analysis of the TCP Gene Family and Their Expression Pattern Analysis in Tea Plant (Camellia sinensis) - Shang, Xiaowen; Han, Zhaolan; Zhang, Dayan; Wang, Ya; Qin, Hao; Zou, Zhongwei; Zhou, Lin; Zhu, Xujun; Fang, Wanping; Ma, Yuanchun (Frontiers in Plant Science, 2022)
TEOSINTE BRANCHED1/CYCLOIDEA/PCF (TCP) transcription factors TEOSINTE BRANCHED1/CYCLOIDEA/PCF have been suggested to control the cell growth and proliferation in meristems and lateral organs. A total of 37 CsTCP genes were identified and divided into two classes, class I (PCF, group 1) and class II (CIN CYC/TB1, groups 2, and 3). The residues of TEOSINTE BRANCHED1/CYCLOIDEA/PCF of Camellia sinensis (Tea plant) (CsTCP) proteins between class I and class II were definitely different in the loop, helix I, and helix II regions; however, eighteen conserved tandem was found in bHLH. There are a large number of CsTCP homologous gene pairs in three groups. Additionally, most CsTCP proteins have obvious differences in motif composition. The results illuminated that CsTCP proteins in different groups are supposed to have complementary functions, whereas those in the same class seem to display function redundancies. There is no relationship between the number of CsTCP gene members and genome size, and the CsTCP gene family has only expanded since the divergence of monocots and eudicots. WGD/segmental duplication played a vital role in the expansion of the CsTCP gene family in tea plant, and the CsTCP gene family has expanded a lot. Most CsTCP genes of group 1 are more widely and non-specifically expressed, and the CsTCP genes of group 2 are mainly expressed in buds, flowers, and leaves. Most genes of group 1 and some genes of group 2 were up-/downregulated in varying degrees under different stress, CsTCP genes of group 3 basically do not respond to stress. TCP genes involved in abiotic stress response mostly belong to PCF group. Some CsTCP genes may have the same function as the homologous genes in Arabidopsis, but there is functional differentiation.